Phonological Accent Features in Anne-Marie’s and Ariana Grande’s YouTube Interviews: A Descriptive Study - Aidhawardini, Lintang Fajar; Prasetyo, Yudy; Sabat, Yuliyanto (Universitas Pahlawan Tuanku Tambusai, 2026)
Accent variation is an important aspect of spoken English, yet descriptive studies of phonological features in spontaneous media interviews remain limited. This study aims to describe the phonological accent features found in the vowels and consonants produced by Anne-Marie (British English) and Ariana Grande (American English) in YouTube interviews. The study employs a qualitative descriptive method using International Phonetic Alphabet (IPA) transcription to analyze pronunciation patterns in spontaneous speech. The data consist of two interview segments: one interview of Anne-Marie (2 minutes 16 seconds) and one interview of Ariana Grande (3 minutes 39 seconds). The findings show that Anne-Marie demonstrates British English features such as /ɒ/ vowels, non-rhoticity, stable /ɪ/ realization, and T-glottalization. In contrast, Ariana Grande displays American English features including /ɑː/ vowels, stable /ɪ/ realization, and rhotic pronunciation. These patterns illustrate how phonological accent features systematically reflect speakers’ linguistic identity in natural communication contexts.